A feature geometric approach to Bondu-so vowel harmony. Issue 1 (6th March 2019) - Green, Christopher R.; Hantgan, Abbie E.
Abstract : Bondu-so (Dogon; Mali) vowel harmony exhibits both typologically and theoretically interesting properties. The language's vocalic system displays surface patterns that implicate a ten-vowel system with an underlying [ATR] contrast at three vowel heights that is not immediately apparent given only mid vowels maintain an [ATR] contrast on the surface. The current paper presents previously unaccounted for data that show alternations associated with Bondu-so vowel harmony correlate not only with the [ATR] specification of a given root vowel, but also with properties of the root-final consonant. We appeal to a combination of featural and prosodic licensing to analyze these outcomes and do so in a modified version of the Parallel Structures Model of feature geometry. The PSM framework has been employed in studies of consonant assimilation and consonant-vowel interaction, but to our knowledge, the current paper is the first to extend it specifically to the analysis of vowel harmony.